Cellulose Acetate of Rice Husk Blend Membranes: Preparation, Morphology and Application - Meri Suhartini; Engela Evy Ernawati; Anisa Roshanova; Haryono Haryono; June Mellawati (Indonesian Journal of Chemistry, 2020)
Cellulose acetate blend membranes in this study synthesized from cellulose acetate (CA) of rice husk and NaA zeolites (Z) with N,N’-Methylene bis acrylamide (MBA) as cross-linker agent and gamma-rays from cobalt-60 source as a reaction initiator. Application of the membrane was carried out to increase the concentration of vetiverol in vetiver oil. The steps in this study were isolation the cellulose rice husk with alkali treatment, delignification, acetylation, preparation the cellulose acetate-NaA zeolites NaA-membrane by inverse phase technique, addition N,N’-Methylene bis acrylamide, and irradiation by gamma-rays. Swelling degree, crosslinking yield, tensile strength, membrane performance, FTIR, and SEM analysis were observed. The results obtained that the optimal irradiation dose for synthesis CA-Z-MBA membrane is 20 kGy. The CA-Z-MBA membrane has swelling degree of 4.44%, the tensile strength of 656.40 kg/cm2, and crosslinking yield of 6.61%. Performance of the CA-Z-MBA membrane reached the flux of 60.58 g/m2.h, and permeate concentration (CP) of 11.67%, the CP increase 5 times from 2.40% to 11.67%.